2012
DOI: 10.1007/s11033-012-1779-5
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of microRNA in the dairy goat (Capra hircus) mammary gland by Solexa deep-sequencing technology

Abstract: microRNAs (miRNAs) perform critical roles in various biological and metabolic processes by regulating gene expression at the post-transcriptional level. To investigate the functional roles of miRNAs in the lactating mammary gland of Capra hircus, a library was constructed from the lactating mammary glands of Laoshan dairy goats (C. hircus) during early lactation. The miRNA expression profiles were systematically screened, and miRNAs were identified and characterized using Solexa deep-sequencing technology and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
48
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(62 citation statements)
references
References 45 publications
14
48
0
Order By: Relevance
“…The dysregulation of miR-143 is implicated in a wide range of malignancies, including various forms of lymphoma, carcinomas of the breast, lung and pancreas and cervical cancer (Tripathi et al 2009;Liu et al 2012;Kapoor 2014). Although miR-143 has been extensively investigated in a variety of pathological tissues, but its specific functions in mammary gland development, lactation and involution remain elusive, and according to our previous studies, miR-143 seemed to be an interesting candidate for involvement in mammary gland development, lactation and involution (Ji et al 2012a(Ji et al , 2012b. In this study, MTT and cell count were used to test the functions of miR-143 on proliferation and viability of dairy goat mammary epithelia cells.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The dysregulation of miR-143 is implicated in a wide range of malignancies, including various forms of lymphoma, carcinomas of the breast, lung and pancreas and cervical cancer (Tripathi et al 2009;Liu et al 2012;Kapoor 2014). Although miR-143 has been extensively investigated in a variety of pathological tissues, but its specific functions in mammary gland development, lactation and involution remain elusive, and according to our previous studies, miR-143 seemed to be an interesting candidate for involvement in mammary gland development, lactation and involution (Ji et al 2012a(Ji et al , 2012b. In this study, MTT and cell count were used to test the functions of miR-143 on proliferation and viability of dairy goat mammary epithelia cells.…”
Section: Discussionmentioning
confidence: 92%
“…The miR-143 sequence was predicted in our previous studies of the miRNA expression profiles of dairy goat mammary gland tissues based on Illumina/Solexa highthroughput sequencing technology deposited in miRBase (Ji et al 2012a(Ji et al , 2012b. Multiple studies have shown that miR-143 is linked to the regulation of a diverse set of processes in vertebrates.…”
Section: Introductionmentioning
confidence: 99%
“…The SOAP software was used to analyze sRNA expression and distribution on the genome. Gene ontology analysis was performed on the predicted target gene candidates of the novel miRNAs using 3 ontologies: molecular function, cellular components, and biological process (Ji et al, 2012). All of the predicted target genes were classified according to KEGG functional annotations, to identify the pathways actively regulated by miRNAs in goat (Kanehisa et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…With the development of sequencing technology and bioinformatics, more and more miRNAs have been identified in animals (Ji et al, 2012). The number of miRNAs found and deposited in miRBase has risen almost exponentially.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation